Synchronicity : the inner path of leadership - Jaworski, Joseph (Berrett-Koehr Pub. San FranciscoUS, 1996)
Spans two decades in the writer's journey of self-discovery. Explores the concept of servant leadership and provides insights about the changes required in both public and institutional leadership for the 21st century.